THE INFLUENCE OF WORK CULTURE TOWARD SELF- CONTROL (LOCUS OF CONTROL) OF CERTIFIED PRIMARY SCHOOL TEACHERS - Sumardi Ahmad; Isjoni Isjoni; M. Yogi Riyantama Isjoni (Education Administration Study Program, School of Postgraduate Studies, Universitas Riau, 2022)
The objective of the study was to analyse how positive and significant the influence of work culture toward self-control (locus of control) of certified teachers at primary schools. The population of this research were 155 certified teachers at primary school in Kuantan Tengah District. Seventy-five certified teachers were randomly selected as samples. The research was undertaken using a correlational research survey design. Data were collected using questionnaires statistically analysed to see if there were any effects on the work culture and teachers’ self-control. This study indicated a significant and positive effect of work culture on primary teachers’ self-control (locus of control). The finding implies that the increase in self-control (locus of control) is possible to achieve by strengthening the work culture.